The effect of learning cycle 5E+Powtoon on students’ motivation: The concept of animal metamorphosis - Koraima Resmol; Marleny Leasa (University of Muhammadiyah Malang, 2022)
During the Covid-19 pandemic period, elementary school students experienced many learning difficulties, which resulted in decreased learning motivation. This study aimed to determine the effect of the 5e+Powtoon learning cycle learning model on learning motivation in science. This quasi-experimental research was conducted at public Elementary School (ES) Teladan Ambon, Maluku. There were two groups, one as the experimental class and another as a control class with 60 students. The research design used was a pretest-posttest non-equivalent control group. The instrument used is a learning motivation questionnaire, with a value of validity = 0.769 and reliability = 0.897. The analysis results with ANCOVA showed the value of Sig = 0.000 > alpha (0.05), so applying the 5E+Powtoon model effect students' learning motivation. Thus, the 5e+Powtoon learning cycle can be recommended to increase elementary school students learning motivation. Further research is suggested to compare student motivation in Maluku with other developed countries by using the 5E model with other online learning applications.